A new species of Fusigobius (Teleostei: Gobiidae) from the Red Sea and Gulf of Aden - Bogorodsky, Sergey V.; Kovačić, Marcelo; Mal, Ahmad O.; Alpermann, Tilman J. (Zootaxa, 2023)
The gobiid species, Fusigobius humerosus sp. nov., is described based on 12 type and 18 non-type specimens collected from the Red Sea and Gulf of Aden. The new species can be distinguished from congeners by a combination of meristic and morphometric characters. The new species was formerly misidentified with F. humeralis: both are characterised by a semitranslucent body; head and body with numerous small dusky orange-yellow spots; a round black spot in humeral region just above base of pectoral fin; and a black spot subequal to pupil diameter at midbase of the caudal fin. However, Fusigobius humerosus sp. nov. differs from F. humeralis by scales on side of nape not extending forward to above posterior margin of preopercle (vs. scales variably extending forward to between above posterior preopercular margin and orbit); first dorsal-fin spine longest (vs. second and third dorsal-fin spines longest); shorter upper jaw; shorter anal-fin spine; and posterior nostril about halfway between orbit and anterior nostril (vs. posterior nostril closer to orbit). The most complete description of the genus Fusigobius is provided. In phylogenetic analyses of publicly available sequences of the barcoding portion of the mitochondrial cytochrome oxidase subunit I (COI) gene, sequences derived from the new species form a separate and well-divergent monophyletic lineage. The resulting COI gene tree further suggests that the new Fusigobius species is phylogenetically most closely related to F. humeralis which forms its sister species in the maximum likelihood tree. Molecular species delimitation of available Fusigobius COI barcodes shows that 19 or 20 hypothetical divergent evolutionary lineages can be deduced depending on the analytical approach (ABGD = 19 and bPTP = 20), indicating a potentially higher taxonomic richness than the presently acknowledged 11 valid species. However, the assignment of available species names for some lineages remains uncertain, highlighting the need for an additional integrative taxonomic research on this genus.